Optimizing Nitrogen-Based Chemical Fertilizer Efficiency Through Microbial Organic Fertilizer (MOF) Integration for Sustainable Oryza sativa Productivity in Rainfed Lowland Fields - Bibit Lilik Lestari; Karyanti Karyanti; Selly Salma; Dwika Nano Hariyanto (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: This study determines the best combination of nitrogen fertilizers and MOF (Microbial Organic Fertilizer) to sustainably increase rice productivity in rainfed lowland regions while minimizing N loss and improving soil health. Excessive application of nitrogen fertilizer contributes to soil degradation; however, MOF can help enhance nutrient uptake efficiency and reduce chemical dependency in rainfed agricultural areas due to its derivation from agricultural waste materials. Objective: To identify the nitrogen fertilization and MOF combination that maximizes Oryza sativa yield in rainfed lowlands while reducing chemical fertilizer use. Specifically, this research aimed to determine the ideal combination ratio of NPK Phonska and mycorrhizae that yields the highest productivity while maintaining an adequate Nitrogen Use Efficiency (NUE). Method: A Randomized Complete Block Design (RCBD) with 25 treatment combinations was conducted in Jember, East Java, Indonesia, as follows: NPK (0–100%) and MOF (0–100%) at three replications. Statistical analysis was performed using ANOVA and DMRT (5%). Results: The combination of 100% NPK and 50–100% MOF showed a significant increase in yield, with the highest yield recorded at 100% NPK and 25% MOF (9,545 kg/ha). The 25% MOF and 75% NPK combination yielded 5,462.5 kg/ha, representing a 25% reduction in fertilizer application without a significant decrease in yield (p < 0.05). Conclusion: The use of 25% MOF combined with 100% nitrogen fertilizer is beneficial for optimizing productivity, decreasing chemical fertilizer use, and promoting sustainable rainfed rice production.